BIOLOGY AND FISHERY OF SILVERBELLY LEIOGNATHUS DUSSUMIERI (VALENCIENNES) FROM GULF OF MANNAR - James, P S B R; Badrudeen, M (Indian Journal of Fisheries, 2011)
•Length-weight relationship of mate and female L. dussumieri was found to be different. Within femallesi, the SimirMure, maturing, mature and spent-recovering females differ from one another in the length-weight relationship. Males weigh comparatively less than females. Among the females, immature, maturing and spentrecovering females weigh more than mature females. This species mainly spawns during April>-Maiy and November-December, Minimum sfefe of maturity for males were found to be 78 mm and for females 83 mm. Generally, females predominate over males in the commercial catches. The counts of mature ova ranged from 805 to 41683 per female. The fecundity-length relationship has; beea studied by three diffrent formulae and it was found that fecundity is better related; to direct cube of length.